Barack and Michelle : portrait of an American marriage - Anderson, Christopher P. (New York : William Morrow, 2009)
One of America's bestselling pop-culture and current-events authors reveals the inside story of the First Couple, in this biography of the history-making family
One of America's bestselling pop-culture and current-events authors reveals the inside story of the First Couple, in this biography of the history-making family
Includes bibliographical references and index
Keywords: Obama, Michelle , -- 1964- -- Marriage; United States. President (2009- : Obama) -- Marriage; Married people -- United States -- Biography; Presidents spouses -- United States -- Biography; Presidents -- United States -- Biography